2015
DOI: 10.3389/fncel.2015.00383
|View full text |Cite
|
Sign up to set email alerts
|

Meninges harbor cells expressing neural precursor markers during development and adulthood

Abstract: Brain and skull developments are tightly synchronized, allowing the cranial bones to dynamically adapt to the brain shape. At the brain-skull interface, meninges produce the trophic signals necessary for normal corticogenesis and bone development. Meninges harbor different cell populations, including cells forming the endosteum of the cranial vault. Recently, we and other groups have described the presence in meninges of a cell population endowed with neural differentiation potential in vitro and, after transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 45 publications
(78 reference statements)
5
59
0
Order By: Relevance
“…During development, their precursor cells merge from mesodermal structures and the neural crest, actively contributing to the differentiation of the brain [1][2][3] . However, meningeal cells may transform to initiate tumors, which represent .…”
Section: Introductionmentioning
confidence: 99%
“…During development, their precursor cells merge from mesodermal structures and the neural crest, actively contributing to the differentiation of the brain [1][2][3] . However, meningeal cells may transform to initiate tumors, which represent .…”
Section: Introductionmentioning
confidence: 99%
“…We have now moved well beyond thinking of them as only protecting the brain and spinal cord from impact damage. Recent work has shown that they are involved in the development of the CNS and contain neural stem cells that are active in all stages of higher vertebrate life (Bifari et al, 2015;Bifari et al, 2016;Borrell & Marin, 2006). It is therefore surprising that we know so little about their development and origin.…”
Section: Discussionmentioning
confidence: 99%
“…This could be achieved by exploiting the findings of elegant studies performed in the brain which showed that cells positive to Nestin are a convenient way to identify neural progenitors. If these cells are present in the spinal meninges then their fate can be again followed by single cell RNAseq analysis (Bifari et al, 2015;Bifari et al, 2016).…”
Section: Developmental Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, strong vimentin expression characterized chicken meninges attached to the cerebellar cortex. Studies in mammals showed that meninges form a wide‐spread niche from where neurogenesis may be induced following physiological stimuli (Bifari et al, 2015) and the involvement of the meninges, particularly the pia mater, has been suggested in the development of the perturbed foliation pattern, possibly via basal lamina stabilization or destabilization (Necchi and Scherini, 2002). Further studies are necessary to clarify the possible role of vimentin in such mechanisms.…”
Section: Discussionmentioning
confidence: 99%